2018
DOI: 10.1371/journal.pbio.2006352
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation in a landrace of maize is supported by a mucilage-associated diazotrophic microbiota

Abstract: Plants are associated with a complex microbiota that contributes to nutrient acquisition, plant growth, and plant defense. Nitrogen-fixing microbial associations are efficient and well characterized in legumes but are limited in cereals, including maize. We studied an indigenous landrace of maize grown in nitrogen-depleted soils in the Sierra Mixe region of Oaxaca, Mexico. This landrace is characterized by the extensive development of aerial roots that secrete a carbohydrate-rich mucilage. Analysis of the muci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
259
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(279 citation statements)
references
References 63 publications
8
259
1
3
Order By: Relevance
“…In boreal forests, this N 2 fixation by cyanobacteria living in symbiosis with mosses can account to up to 50% of total biological N input (DeLuca, Zackrisson, Nilsson, & Sellstedt, ; Santi et al, ; Warshan et al, ). In N‐depleted soils in Mexico, recent work has shown that the mucilage of aerial roots of an indigenous landrace of maize enriched in diazotrophs (Van Deynze et al, ) (Figure ). This mucilage, rich in arabinose, fucose and galactose, can support N 2 ‐fixing activity by the diazotrophs.…”
Section: Plants Acquire Nitrogen By Recruiting Micro‐organisms Througmentioning
confidence: 99%
“…In boreal forests, this N 2 fixation by cyanobacteria living in symbiosis with mosses can account to up to 50% of total biological N input (DeLuca, Zackrisson, Nilsson, & Sellstedt, ; Santi et al, ; Warshan et al, ). In N‐depleted soils in Mexico, recent work has shown that the mucilage of aerial roots of an indigenous landrace of maize enriched in diazotrophs (Van Deynze et al, ) (Figure ). This mucilage, rich in arabinose, fucose and galactose, can support N 2 ‐fixing activity by the diazotrophs.…”
Section: Plants Acquire Nitrogen By Recruiting Micro‐organisms Througmentioning
confidence: 99%
“…The AGP nanoparticles are highly uniform and evenly spread over the attachment area (Lenaghan & Zhang, 2012). Whether Extrafloral nectars secreted by stems, leaves or aerial roots to provide protection and nutrition Many land plant species secrete mucilage through their stems as extrafloral nectar (Deynze et al, 2018;Pierce, 2019). Whether Extrafloral nectars secreted by stems, leaves or aerial roots to provide protection and nutrition Many land plant species secrete mucilage through their stems as extrafloral nectar (Deynze et al, 2018;Pierce, 2019).…”
Section: Aerial Adhesive Mucilages Facilitating Climbing Motionmentioning
confidence: 99%
“…The firm attachment is further supported by cellulose microfibrildependent shape changes of adventitious root hairs at the attachment interface (Melzer et al, 2010), accentuating the possibility that structural and chemical features have been finetuned together to form an attachment organ that meets the special needs of climbing plants. Despite their name, extrafloral nectars are not involved in attracting pollinators but rather entice invertebrates such as ants or wasps to protect the plants from herbivorous predators (Gaume & Forterre, 2007;Llhan et al, 2007) or to supplement their diet with nitrogen by trapping insects or cultivating microbial symbionts (Adlassnig et al, 2010;Deynze et al, 2018). Despite their name, extrafloral nectars are not involved in attracting pollinators but rather entice invertebrates such as ants or wasps to protect the plants from herbivorous predators (Gaume & Forterre, 2007;Llhan et al, 2007) or to supplement their diet with nitrogen by trapping insects or cultivating microbial symbionts (Adlassnig et al, 2010;Deynze et al, 2018).…”
Section: Aerial Adhesive Mucilages Facilitating Climbing Motionmentioning
confidence: 99%
See 2 more Smart Citations